Voices from the Perspective of the Ancient Rhetoricians between the Linguistic Reference and the Procedural Specificity: the ''SIR ALFASSAHA'' by Ibn Sinan al-Khafaji as a Model - Terchag, Souad (Journal of Human Sciences, 2023)
Rhetoricians have benefited greatly from phonetics being the criterion for the eloquence of the word as well as the sentence. They even devoted sections in their writings to discussing this subject. It should be noted that rhetoricians approached the phoneme based on rhetorical aesthetic issues, since they know very well that rhetorical discourse with its aesthetic and pragmatic dimensions is only a speech reported by the voice. So, they emphasised the letter and its effect on meaning; and its function in speech. Ibn Sinan Al- Khafaji is one of the famous rhetoricians who linked the phoneme to rhetoric by presenting the secret of eloquence from the phoneme. Accordingly, he mentioned its characteristics, points of articulation and effect on speech based on the research of linguists and rhetoricians. So, it became a prominent topic in the studies made about phonetics but from a rhetorical side.